2016
DOI: 10.5296/rae.v8i3.9806
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Well-being and Its Determinants in China: An Empirical Study Based on Survey Data

Abstract: Using household survey data collected in 2013, this paper empirically investigates the determinants of individual subjective well-being in China, where there has been rapid economic development over the past three decades. The main results are as follows. First, factors such as good health, marital status, life satisfaction, body mass index, physical exercise, and expectations of inflation are all significantly correlated with the reported level of happiness. Second, income has no significant effect on the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
(37 reference statements)
0
5
2
1
Order By: Relevance
“…13,14,16 But studies from rural India and elsewhere have also reported men to be less happy than females. 17,18 In the present study no differences were noted due to literacy and occupation parameters but these were contrary to studies from other countries. 13,17,19 The probable explanation would be that, less educated people had more leisure time to engage themselves in other activities which could be the source of happiness.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…13,14,16 But studies from rural India and elsewhere have also reported men to be less happy than females. 17,18 In the present study no differences were noted due to literacy and occupation parameters but these were contrary to studies from other countries. 13,17,19 The probable explanation would be that, less educated people had more leisure time to engage themselves in other activities which could be the source of happiness.…”
Section: Resultscontrasting
confidence: 99%
“…This finding was well supported by reported literature as well. 13,14,17,18,25 Individuals who did not smoke or ex-smokers were happier although the results were not statistically significant in the current study. Higher levels of nicotine dependence was associated with lower levels of happiness, as reported from the former Soviet Union, while a work place study from New Zealand reported smoking to be negatively associated with happiness.…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…Likewise, LS studies in China have expanded and are gradually advancing to the standard of research conducted in most developed countries. The effect of most determinants of LS in China is generally comparable to findings worldwide [18,19]. Researchers have probed into these general determinants of life satisfaction across different population groups and geographical segregations such as rural residents and urban citizens in addition to the dynamics of demographic transitions such as rural-urban migration.…”
Section: Life Satisfaction In Chinamentioning
confidence: 87%
“… Blanchflower and Oswald (2008) , Brockmann et al (2009) , Graham and Felton (2006) , Guriev and Zhuravskaya (2009) , Lane (2017) , Liang and Shen (2016) , Liu et al (2013) , Nikolaev and McGee (2016) , Ohtake and Tomioka (2004) , Oshio and Kobayashi (2011) , Stets and Trettevik (2016) and Wang et al (2015) .…”
Section: Uncited Referencesmentioning
confidence: 99%